Genetic Variation of the First Generation of Rodent Tuber (Typhonium flagelliforme Lodd.) Mutants Based on RAPD Molecular Markers - DANNY LAURENT; RAGAPADMI PURNAMANINGSIH; IRENG DARWATI; NESTI FRONIKA SIANIPAR (Bogor Agricultural University, Indonesia, 2015)
Rodent tuber (Typhonium flagelliforme Lodd.) is a herbal plant from the Araceae family. The plant has high medical potential and is effective to cure cancer. However, the low level of its genetic variation limits its exploration for desirable traits. The low level of genetic variation in Rodent tuber is mainly due to its asexual reproduction system. It usually reproduces vegetatively via tuber separation. Therefore, gamma irradiation had been applied to rodent tuber in vitro to increase its genetic diversity. The objective of this study was to analyze the genetic diversity of the first generation (MV1) of gamma irradiated rodent tuber mutant using random amplified polymorphic DNA (RAPD) markers. A total of 14 mutant DNA samples were analyzed with 14 RAPD primers. The result showed that 67 out of 123 DNA bands were polymorphic among mutant lines. Based on cluster analysis these mutants showed 0.78-0.97 genetic similarity. Cutting of dendogram at genetic distance of 0.89 produced four main clusters. Mutants with high genetic variation are now available. This increases the opportunity of obtaining mutant lines with high anti-cancer activity.